Peran Digital Marketing Skill dalam Meningkatkan Daya Saing Lembaga Perbankan Syariah - Zuhrinal M. Nawawi; Miratul Imaniah (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research uses a qualitative method to explore the role of digital marketing skills in enhancing the competitiveness of Islamic banking institutions in the era of digital transformation. The rapid development of information technology requires financial institutions, including Islamic banks, to adapt to digital-based marketing strategies to remain competitive in the market. Digital marketing skills such as social media management, search engine optimization (SEO), content marketing, and digital data analysis have become essential in effectively reaching customers and building strong brand awareness. This study was conducted through in-depth interviews with Islamic banking practitioners and analysis of documentation related to digital marketing strategies. The findings reveal that mastering digital marketing skills significantly helps Islamic banking institutions expand their market reach, improve customer engagement, and strengthen their competitive position in the financial industry. Moreover, the proper implementation of digital marketing also enhances promotional cost efficiency and encourages product and service innovation based on customer needs. These findings serve as a vital reference in developing more relevant Islamic marketing strategies for the current era.